Crônicas de Tostão: o futebol, a literatura e a vida - Lima, Leandro Siqueira (2016)
The study proposes a starting point for the interpretation of Tostão's chronicles. The analysis of the studied chronicles demand to see them always as part of a larger whole, and that, therefore, the whole set is studied, from the understanding that there is a conscious program on the part of the chronicler Tostão. For such, the analysis seeks, on the hypothesis of a reading of the contours as well as the points of support of his writing, to recognize aspects of brazilian literature – in which a certain story he attempted to tell - of the football literature as well as the football chronic that are in dialogue with the texts written in newspapers by Tostão. The writing and reflection gestures carried out by Tostão in analysing football, literature and life allow us to see an attempt to reassemble and resize both the senses of literary genres, the trivial formula to discuss football, as well as the common optics in order to understand the aspects that underlie the current social structures.